Accelerating ions with high-energy short laser pulses from submicrometer thick targets. (12th December 2016) - Wagner, F.; Brabetz, C.; Deppert, O.; Roth, M.; Stöhlker, T.; Tauschwitz, An.; Tebartz, A.; Zielbauer, B.; Bagnoud, V.
Abstract : Using the example of the PHELIX high-energy short pulse laser we discuss the technical preconditions to investigate ion acceleration with submicrometer thick targets. We show how the temporal contrast of this system was improved to prevent pre-ionization of such targets on the nanosecond timescale. Furthermore the influence of typical fluctuations or uncertainties of the on-target intensity on ion acceleration experiments is discussed. We report how these uncertainties were reduced by improving the assessment and control of the on-shot intensity and by optimizing the positioning of the target into the focal plane. Finally we report on experimental results showing maximum proton energies in excess of 85 MeV for ion acceleration via the target normal sheath acceleration mechanism using target thicknesses on the order of one micrometer.